Gambaran Kecemasan Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa di Rumah Sakit Santa Elisabeth Medan Tahun 2023 - Sinta, Okfi Maya; Tondang, Gryttha; Siringoringo, Magda (Prodi Keperawatan Purwokerto, 2023)
Background: Chronic renal failure is the presence of progressive kidney damage in the human body characterized by uremia (urea in other wastes circulating in the blood and its complications. Hemodialysis is a high-tech substitute for removing metabolic waste from human blood circulation such as water, sodium, potassium, hydrogen, urea, creatinine, uric acid, and other substances through aÂ Â semi-membrane Permeable as a separator of blood and dialysate fluid in artificial kidneys where diffusion, osmosis and ultra filtration processes occur.Â Proses hemodialysis 1-3 times a week and each time takes 2-5 hours, this activity will continue 3-4 hours per therapy. Anxiety in hemodialysis patients arises because during the hemodialysis process they see tubes that are fed by blood entering the body, they also have to pay costs when undergoing hemodialysis, and uncertainty about recovery. Objective: To find out the anxiety picture of chronic kidney failure patients undergoing hemodialysis at Santa Elisabeth Medan Hospital 2023. Methods: To find out the anxiety picture of chronic kidney failure patients undergoing hemodialysis at Santa Elisabeth Medan Hospital 2023. Method: This study is a descriptive research. Sampling using Total Sampling technique amounting to 40 respondents. The research instrument uses Zung Self Rating Scale (ZSAS) questionnaire. Results: The results of this study found that the anxiety of chronic kidney failure patients undergoing hemodialysis at the Santa Elisabeth Hospital in Medan in 2023 mostly experienced mild anxiety as much as 50.0%, moderate anxiety as much as 40.0% and severe anxiety as much as 7.5% and panic as much as 2.5%. Conclusion: This researcher illustrates that the anxiety level of patients with chronic kidney failure undergoing hemodialysis is influenced by characteristics such as age, type of health, and education.